Information sharing via electronic health records in team-based care: the patient perspective. (4th March 2021) - Sanyer, Osman; Butler, Jorie M; Fortenberry, Katherine; Webb-Allen, Tatiana; Ose, Dominik
Abstract: Purpose: Team-based care offers potential improvements in communication, care coordination, efficiency, value and satisfaction levels of both patients and providers. However, the question of how to balance the need for information in team-based care without disregarding patient preferences remains unanswered. This study aims to determine patients' perceptions of information sharing via electronic health records (EHRs) in team-based care. Methods: This qualitative study used a focus group approach. Participants were primary care patients and representative members from minority groups (ethnic, racial or social). Audio recordings of the sessions were transcribed and coded consistent with thematic analyses. Results: The analysis revealed that the participants in the focus groups had diverging levels of understanding and personal beliefs around five major themes including (i) patient's understanding of the care team, (ii) perceptions of electronic health records, (iii) defining basic health care information, (iv) sharing information with the health care team and (v) patient's trust in doctors and the health care system. Conclusions: The participants of our focus groups value team-based care and view patients as a critical part of those teams. With respect to electronic health records, our participants recognized their importance but had concerns about inaccuracies and limited options to correct errors in their records. In general, participants were willing to share basic information but disagreed about what information should be considered to be basic. Moreover, based on their trust and comfort level, many participants want to control what information is recorded and shared in the electronic health record.